My mummy is autistic : a picture book and guide about recognising and understanding difference - Grace, Heath; Grace, Joanna (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This original and imaginative book has been created by five-year-old Heath and his mother Joanna, who has autism, to explain the different ways in which autistic and neurotypical people understand language. In his simple and uncomplicated style, accompanied by bright and colourful illustrations, Heath explains why his mother's brain understands words at a different rate than his own, and how he helps her to comprehend and say the right things. Heath's work is accompanied by explanatory notes exploring Joanna's own experience of autism and language. Key features include: A unique exploration of language processing differences told through the eyes and mind of a child. Bright, colourful pictures and simple language, perfect for inspiring conversations about neurodiversity between people of all ages. Explanatory text that can be read alongside the story. The combination of story and commentary makes this book a unique tool for all people seeking to explain and understand difference, regardless of age and experience. Although focusing on autism as an example of neural difference, it can be used to explain and celebrate neurodiversity in all its forms and will help build relationships across the divide of neurological difference"--
"A Speechmark Book" -- cover.
OCLC-licensed vendor bibliographic record.
Keywords: Grace, Joanna -- Mental health; Autism -- Juvenile literature; PSYCHOLOGY / Psychopathology / Autism